The Effect of The Music Used in The TV Serials on The Watching-Rate of The Young Spectators - Imik, Nural; Yagbasan, Mustafa (Istanbul Univ, 2007)
Music is a branch of art and at the same time, a communication organ. Music has got a lot of function. It has been profited by many branches because of its power. One of these branches is communication. Music creates a communication process and sends messages both to the composer and to the listeners within the process it is formed and afterwards. Communicative side of the music has been used in serials and cinemas. Especially at present, it is common to use music on television serials and at cinema films. It can be said lots of films are remembered because of their music. There is an effect of the film music to the spectators as much as the film. But, there is a limited research about this subject. Nowadays, film music is an inseperable part of the cinema and the serials. Film music and its effect on the spectator should be dealt with in detail so that the music and the film be understood better. Whether the effect of the music used in serials has a role or not on the rate of the serials' being watched is a matter of discussion. In this study, the effect of the music used in TV serials on the watching-rate of the young spectators has been measured. A Questionnaire has been prepared for this purpose and applied to the students at Firat University, Elazig. Obtained data was analyzed on Spss program. As a result of that analysis, the findings were significant on the effects of the film-music on the young spectators.
Keywords: Music; Serials; Film Music